(untitled) (Economics and region, 2022)
The labor market is understood as a system of social relations associated with the hiring and supply of labor, or its purchase and sale. The price of labor is wages. On the labor market one side (sellers) is represented by persons looking for suitable work, the other side (buyers) is represented by employers – entrepreneurs or their representatives. The labor market is in constant motion. The processes that take place in the labor market are inseparably connected with the demographic situation in the country, the dynamics of various age and gender groups, birth and death rates, and in the case of Ukraine, the global pandemic and full-scale war have also changed the labor market. The purpose of the article was to study the general trends in the labor market of Ukraine (the number of employed and unemployed) with a separate immersion in the field of metallurgical production. The overall system of the labor market in Ukraine is ambiguous and constantly changing under the influence of mostly external factors. The system was affected by the first invasion in 2013-14, the global COVID-19 pandemic and active hostilities in the country in connection with the full-scale invasion of Russia. By 2019, the number of unemployed in Ukraine was gradually decreasing, but the pandemic hit small businesses and the service sector hard, causing many people to lose their jobs. The situation on the labor market did not have time to stabilize due to the outbreak of the war, which had an immeasurable impact on the entire country. Many people were killed, injured, or lost their homes and businesses, which will certainly affect the future picture of the Ukrainian labor market. It will take decades to rebuild the country’s workforce. Separately, the metallurgical industry was considered in comparison with the industry as a whole. In this sector, the employment situation is constantly deteriorating, as people prefer more comfortable working conditions than the factories can offer. And after the pandemic, various remote jobs, especially in the IT sector, gained the most popularity. Steel mills cannot operate remotely, so the outflow of people from this area will continue to increase.